Urban Growth in Onaizah City (2002-2018) – An applied study was performed by using remote sensing technology – - Al-Kharafi, Abdullah Abdul Mohsen Hamad (Journal of natural sciences, life and applied sciences, 2021)
This study aims to estimate the value of the urban growth in Onaizah city throughout 2002-2018, identifying the urban growth trends during this period by spatial techniques. The study is based mainly on the spatial analysis method through using remote sensing technology tools, in addition to the historical method. The study relied on satellite visualizations derived from (Land sat satellite 5). ERDAS IMAGINE program and Geographical information systems (GIS) were used to conduct a number of statistical methods such as clipping, processing, discovering change, and producing final maps. Geographical information systems (GIS) technology was also used to produce the final maps. The results of the study revealed that the urban mass areas increased significantly in 2018 to 72 km2 by comparing with the previous period in 2002 which was (43.5 km2) with a rate of (60.4%), The study also showed that urban growth was concentrated in the city center approximately in 2002, but in 2018, accelerated urban expansion appeared from all directions, especially the eastern and northern regions, due to the new plans, and the absence of natural and human obstacles, as sand dunes and farms (orchards) limit urban growth in the western and southern regions. the annual urban growth rate reached (3.2%), therefore, the urban areas in Onaizah city will increase after approximately 17 years, after applying the well-known rule of seventy. The study highlighted on the necessity for integration by using the modern spatial techniques "the remote sensing technology and geographic information systems" in the future urban and population studies to establish an integrated database for the study area to be presented to decision makers to take appropriate decisions.